Modeling anesthesia and pavilion surgical units in a Chilean hospital with Specification and Description Language. (August 2013) - Leiva, Jorge; Fonseca i Casas, Pau; Ocaña, Jordi
This paper addresses the problem of formally modeling processes related to the operation of surgical pavilions and an anesthesia unit in a Chilean hospital. To perform this modeling, we used Specification and Description Language (SDL), which resulted in a graphic layout consisting of one system, 11 blocks, 52 processes, 135 channels of communication, and 137 information signals. The model includes as system environment to the emergency units, clinical services, and support units. The model was created to document and understand the tacit knowledge of the personnel working in the anesthesia and pavilion surgical units. The aim of the proposed methodology was to design a model that can represent the system in a modular and standard way and that will also assist with hospital management and facilitate simulation.